2014
DOI: 10.1073/pnas.1412910111
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblastic reticular cells of the lymph node are required for retention of resting but not activated CD8 + T cells

Abstract: Fibroblastic reticular cells (FRCs), through their expression of CC chemokine ligand (CCL)19 and CCL21, attract and retain T cells in lymph nodes (LNs), but whether this function applies to both resting and activated T cells has not been examined. Here we describe a model for conditionally depleting FRCs from LNs based on their expression of the diphtheria toxin receptor (DTR) directed by the gene encoding fibroblast activation protein-α (FAP). As expected, depleting FAP + FRCs causes the loss of naïve T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
121
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 39 publications
8
121
0
1
Order By: Relevance
“…A recent report by Denton et al (59) provided some validation to this hypothesis by showing a modest reduction in MPEC percentages following FRC depletion during the late phase of an ongoing influenza virus infection. Interestingly, FRC ablation reduced the percentage of MPECs without negatively impacting the abundance of short lived effector cells (59). Selective reduction of MPECs likely occurred in response to decreased FRC-derived IL-7, which is known to support MPEC formation (60) (Fig.…”
Section: Introductionmentioning
confidence: 84%
“…A recent report by Denton et al (59) provided some validation to this hypothesis by showing a modest reduction in MPEC percentages following FRC depletion during the late phase of an ongoing influenza virus infection. Interestingly, FRC ablation reduced the percentage of MPECs without negatively impacting the abundance of short lived effector cells (59). Selective reduction of MPECs likely occurred in response to decreased FRC-derived IL-7, which is known to support MPEC formation (60) (Fig.…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, once T cells are activated, they down-regulate LN retention signals such as CCR7 and thus are primed to egress from the reactive LN and mobilize into the circulation. Interestingly, a study recently demonstrated that naive and effector T cells respond to CCR7 cues differently (32). When CCL19-and CCL21-expressing fibroblastic reticular cells (FRCs) were conditionally depleted, it resulted in the loss of naive, but not effector, T cells from the LN.…”
Section: Discussionmentioning
confidence: 99%
“…When CCL19-and CCL21-expressing fibroblastic reticular cells (FRCs) were conditionally depleted, it resulted in the loss of naive, but not effector, T cells from the LN. The authors (32) suggested that reduced expression of S1PR1, rather than CCR7 signaling, influenced the retention of antigen-specific T cells until they were ready to leave the LN. Therefore, we asked the important question: In light of the infection-induced inflammatory environment, are effector T cells that lack retention signals and are poised to exit the dLN dependent on S1PR1 for egress after a local viral infection?…”
Section: Discussionmentioning
confidence: 99%
“…Fearon's group (212) has elegantly shown that conditional deletion of Pdpn + FAP + FRCs in the early (but not established) phases of the response to influenza severely compromises the CD8-mediated host response. Similarly, deletion of LTβR in lymph node FRCs results in impaired immune responses to viral infections (131,213).…”
Section: What Are the Role And Origin Of Stromal Cells In Secondary Amentioning
confidence: 99%